Occurrence of Es over Taipei - 黃胤年; Yinn-Nien Huang (交大學刊編輯委員會, 1966)
Using the foEs data in the period March 1960-August 1964, the diurnal, seasonal, and solar cycle variations of the percent occurrence of foEs greater than 5 Mc/s over Taipei were studied. The results were about the same as those of the other Asian stations ever reported. The correlations between P and R as well as between P and Ap were also studied. The results show slight negative correlations. No significant correlation was found between the daily geomagnetic activity and daily occurrence of Es. Comparing the present results with those obtained for another epoch of the solar cycle, it seems to conclude that the correlation of P on R and that of daily geomagnetic activity on daily occurrence of Es are different epoch of the solar cycle.